2003
DOI: 10.1016/s0002-9440(10)63847-3
|View full text |Cite
|
Sign up to set email alerts
|

Global Expression Profiling of Fibroblast Responses to Transforming Growth Factor-β1 Reveals the Induction of Inhibitor of Differentiation-1 and Provides Evidence of Smooth Muscle Cell Phenotypic Switching

Abstract: Transforming growth factor-beta1 (TGF-beta1) plays a central role in promoting extracellular matrix protein deposition by promoting the transformation of fibroblasts to myofibroblasts. To gain new insights into the transcriptional programs involved, we profiled human fetal lung fibroblast global gene expression in response to TGF-beta1 up to 24 hours using oligonucleotide microarrays. In this report, we present data for 146 genes that were up-regulated at least twofold at two time points. These genes group int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
175
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(194 citation statements)
references
References 76 publications
(79 reference statements)
19
175
0
Order By: Relevance
“…After reaching its peak, Id1 protein level gradually decreased even with the presence of TGF-β1. In accordance with previous reports [5,27], the Id1 protein level at 4 h after TGF-β1 treatment was below the basal level, indicating that the Id1 gene was repressed or Id1 protein was rapidly degraded. Thus, Id1 protein is transiently induced by TGF-β1 in various human cell lines.…”
Section: Id1 Is Induced By Tgf-β1 In Various Human Epithelial Cell Linessupporting
confidence: 92%
See 2 more Smart Citations
“…After reaching its peak, Id1 protein level gradually decreased even with the presence of TGF-β1. In accordance with previous reports [5,27], the Id1 protein level at 4 h after TGF-β1 treatment was below the basal level, indicating that the Id1 gene was repressed or Id1 protein was rapidly degraded. Thus, Id1 protein is transiently induced by TGF-β1 in various human cell lines.…”
Section: Id1 Is Induced By Tgf-β1 In Various Human Epithelial Cell Linessupporting
confidence: 92%
“…Although previous studies have reported both repression and induction of the Id1 gene by TGF-β [5,27], it is a dominant view that TGF-β primarily represses Id1 transcription [5]. Most of these studies focus on the regulation of the Id1 gene with prolonged TGF-β1 treatment (e.g.…”
Section: Id1 Is Induced By Tgf-β1 In Various Human Epithelial Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased TNF␣ activity in p53 K317R thymocytes is also consistent with the observed lack of change in WARS, TCF7, and ETFDH protein levels after IR; all of these proteins are indirectly regulated by TNF␣ (53)(54)(55)(56)(57)(58). Finally TNF␣ has been shown to induce the expression of TGF␤1 (59), which has been shown to increase the expression of FABP5 and SSRP1 (60,61), two additional proteins that exhibit the same pattern. Thus, the proteins affected differently by IR in wild type compared with mutant thymocytes suggest a change in p53 activity and a decrease in TNF␣ signaling.…”
Section: Discussionsupporting
confidence: 74%
“…Since the regulation of Id1 expression by TGF-b occurs in a cell-type-specific manner (Chambers et al, 2003;Kurisaki et al, 2003), we tested if this is also the case for activin. Therefore, we treated primary human dermal fibroblasts with either activin A or TGF-b1 for different time periods and subjected the cell lysates to Western blotting.…”
Section: Resultsmentioning
confidence: 99%